Adolescents with HIV and transition to adult care in the Caribbean, Central America and South America, Eastern Europe and Asia and Pacific regions - Bailey, Heather (J Int AIDS Soc, 2017)
Introduction: The HIV epidemics in the Caribbean, Central America and South America (CCASA), Eastern Europe (EE) and Asia and Pacific (AP) regions are diverse epidemics affecting different key populations in predominantly middle-income countries. This narrative review describes the populations of HIV-positive youth approaching adolescence and adulthood in CCASA, EE and AP, what is known of their outcomes in paediatric and adult care to date, ongoing research efforts and future research priorities. Methods: We searched PubMed and abstracts from recent conferences and workshops using keywords including HIV, transition and adolescents, to identify published data on transition outcomes in CCASA, EE and AP. We also searched within our regional clinical/research networks for work conducted in this area and presented at local or national meetings. To give insight into future research priorities, we describe published data on characteristics and health status of young people as they approach age of transition, as a key determinant of health in early adulthood, and information available on current transition processes. Results and discussion: The perinatally HIV-infected populations in these three regions face a range of challenges including parental death and loss of family support; HIV-related stigma and socio-economic disparities; exposure to maternal injecting drug use; and late disclosure of HIV status. Behaviourally HIV-infected youth often belong to marginalized sub-groups, with particular challenges accessing services and care. Differences between and within countries in characteristics of HIV-positive youth and models of care need to be considered in comparisons of outcomes in young adulthood. The very little data published to date on transition outcomes across these three regions highlight some emerging issues around adherence, virological failure and loss to follow-up, alongside examples of programmes which have successfully supported adolescents to remain engaged with services and virologically suppressed. Conclusions: Limited data available indicate uneven outcomes in paediatric services and some shared challenges for adolescent transition including retention in care and adherence. The impact of issues specific to low prevalence, concentrated epidemic settings are poorly understood to date. Outcome data are urgently needed to guide management strategies and advocate for service provision in these regions.